Catena manuscripts of the Greek New Testament a catalogue - Parpulov, Georgi 1970- (Gorgias Press, 2021)
"The book is a synoptic catalogue of a large class of Greek manuscripts: it describes all pre-seventeenth century copies of the Greek New Testament in which the biblical text is accompanied by commentary. Manuscripts where this commentary consists of combined excerpts (catena) from the works of various authors are described in particular detail. Those that have similar content are grouped together, so that the potential relatives of any given manuscript can be easily identified. Several previously unknown types of catenae are distinguished and a number of previously unstudied codices are brought to light for the first time. To ensure its longer shelf-life, the volume systematically references on-line electronic databases (which are regularly updated). It will be of use to anyone interested in Byzantine book culture and in biblical exegesis."
Keywords: Geschichte Anfänge-1600; Handschrift; Katene; Bible / New Testament / Manuscripts / Catalogs; Bible / New Testament / Commentaries / Bibliography / Catalogs; Manuscripts, Greek; Catenae